A cell-based microarray to investigate combinatorial effects of microparticle-encapsulated adjuvants on dendritic cell activation. Issue 9 (8th October 2015) - Acharya, Abhinav P.; Carstens, Matthew R.; Lewis, Jamal S.; Dolgova, Natalia; Xia, C. Q.; Clare-Salzler, Michael J.; Keselowsky, Benjamin G.
Abstract : Experimental vaccine adjuvants are being designed to target specific toll-like receptors (TLRs) alone or in combination, expressed by antigen presenting cells, notably dendritic cells (DCs). Abstract : Experimental vaccine adjuvants are being designed to target specific toll-like receptors (TLRs) alone or in combination, expressed by antigen presenting cells, notably dendritic cells (DCs). There is a need for high-content screening (HCS) platforms to explore how DC activation is affected by adjuvant combinations. Presented is a cell-based microarray approach, "immunoarray", exposing DCs to a large number of adjuvant combinations. Microparticles encapsulating TLR ligands are printed onto arrays in a range of doses for each ligand, in all possible dose combinations. Dendritic cells are then co-localized with physisorbed microparticles on the immunoarray, adherent to isolated islands surrounded by a non-fouling background, and DC activation is quantified. Delivery of individual TLR ligands was capable of eliciting high levels of specific DC activation markers. For example, either TLR9 ligand, CpG, or TLR3 ligand, poly I:C, was capable of inducing among the highest 10% expression levels of CD86. In contrast, MHC-II expression in response to TLR4 agonist MPLA was among the highest, whereas either MPLA or poly I:C, was capable of producing among the highest levels of CCR7 expression, as well as inflammatory cytokine IL-12. However, in order to produce robust responses across all activation markers, adjuvant combinations were required, and combinations were more represented among the high responders. The immunoarray also enables investigation of interactions between adjuvants, and each TLR ligand suggested antagonism to other ligands, for various markers. Altogether, this work demonstrates feasibility of the immunoarray platform to screen microparticle-encapsulated adjuvant combinations for the development of improved and personalized vaccines.